EFEKTIVITAS STRATEGI KOMUNIKASI KONSULTAN DALAM PROGRAM BANTUAN LANGSUNG MASYARAKAT PNPM MANDIRI PERKOTAAN DI KOTA RAHA KABUPATEN MUNA - Atnan, Nur (Sawala : Jurnal Administrasi Negara, 2015)
The objectives of this research was to identify the effectiveness of consultant?s communication strtegy in giving proper comprehension to the society about BLM PNPM-MP and to identify the effectiveness distinction of the four applied communication methods in communication strategy, that are informative method, educative method, persuasive method and mixed method (informative and persuasive methods). The method used in this research was mixed method (Quantitative and Qualitative). The total number of samples in this research were 30 for each communication method applied and determining randomly. The informant for qualitative approach consisted of 6 respondents. The data of the research were analyzed using descriptive statistic and anova. The results of the research showed that the consultant?s communication strategy was ineffective because every communication methods applied still used single media strategy. From four communication methods applied, educative method had higher such as informative method, persuasive method and mixed method (informative and persuasive methods).